Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/497263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blockade of β-adrenergic receptor signaling improves cancer vaccine efficacy through its effect on naive CD8+T-cell priming

Abstract: β-adrenergic receptor (β-AR) signaling, by acting directly on tumor cells and angiogenesis, has been showed to exert pro-tumoral effects. Growing evidence also suggests that β-AR expressed by immune cells affect the associated anti-tumor immune response. However, how and where β-AR signaling impinges the anti-tumor immune response is still unclear. Using a mouse model of vaccine-based immunotherapy, we show here that propranolol, a non-selective β-blocker, strongly improved the efficacy of the vaccine by enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…As adrenergic signalling mostly plays a suppressive role in T cells, adrenergic signalling is well studied in various diseases like cancer and other autoimmune diseases. Propranolol, a β-blocker, has been found to increase vaccine efficacy in a murine model by blocking adrenergic signalling in naïve CD8 + T cells ( Daher et al, 2018 ). It is also demonstrated that inhibition of adrenergic signalling decreases the number of PD-1 in CD8 + T cells and helps in checkpoint inhibition therapy ( Bucsek et al, 2017 ).…”
Section: Expression Of Adrenergic Receptors On Various Immune Cellsmentioning
confidence: 99%
“…As adrenergic signalling mostly plays a suppressive role in T cells, adrenergic signalling is well studied in various diseases like cancer and other autoimmune diseases. Propranolol, a β-blocker, has been found to increase vaccine efficacy in a murine model by blocking adrenergic signalling in naïve CD8 + T cells ( Daher et al, 2018 ). It is also demonstrated that inhibition of adrenergic signalling decreases the number of PD-1 in CD8 + T cells and helps in checkpoint inhibition therapy ( Bucsek et al, 2017 ).…”
Section: Expression Of Adrenergic Receptors On Various Immune Cellsmentioning
confidence: 99%